Editorial - Martínez Llaque, José (2020)
Pluriversidad appears with the fifth edition, in a tragic juncture for the country and the world in which the coronavirus pandemic has place the life defense as the principal aim of the government and their citizens. In this context, our University reinforces all his human abilities and its tools to attenuate and overcome the critical factors that threaten the Peruvian society health and economy.  Although reality is demonstrating that overcome this pandemic by itself is not enough, it is necessary to build a world in which liberty and justice could let us show in what kind of society we would like to live. And this could only be reach distinguishing the different social and political force that look for a different culture in relation to the one we are living in. Therefore Pluriversidad will continue to call for professional and intellectual staff from different areas to debate and propose alternatives in different aspects associated to economy, politics and culture